Compact latent heat exchanger for the fast supply of hot water with serpentine tubes in shape-stabilized composite phase change material and auxiliary electric heating. (5th July 2022) - He, Yangjing; Yuan, Wenhui; Cao, Jiahao; Li, Li; Ling, Ziye
Highlights: A composite phase change material-based heat exchanger is designed. The composite phase change material owns a large enthalpy of 252 J/g. An electric heating film is introduced to improve the heating efficiency. Abstract: To realise a fast supply of hot water, this study proposes a compact latent heat exchanger. This heat exchanger consists of a certain number of heat-exchange plates. In each plate, serpentine tubes are wrapped with an inorganic composite phase change material (CPCM), Ba(OH)2 ·8H2 O/modified expanded graphite (MEG). An auxiliary electric heating film is attached to the face of the entire heat exchanger to improve the heating efficiency. The parameters of the plate, such as thickness, tube pass number, thermo-physical properties of the CPCM, flow rate, auxiliary heating power size, and position are numerically evaluated to achieve the best performance of this heat exchanger. The reliability of the simulation method is verified by comparing the simulated results with the experimental data in previous study. The simulation results indicate that a plate with a thickness of 15 mm, plate tube pass number of 10, and CPCM with a Ba(OH)2 ·8H2 O mass fraction of 85.8 wt% is the optimal choice. Based on the optimal conditions, 196.48 kg of hot water over 40 ℃ can be produced in 875 s and the average power reaches 23 kW. Furthermore, with the addition of a heating film (3600 W), the mass of heated water can be increased by nearly 50 kg.